ANALISIS KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Ardhyatama, Airlangga; Widyartati, Penta; Setiyanti, Sri Wiranti; Suryatama, Fajar (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Abstract. The research background is due to the failure to achieve the annual motor vehicle tax realization target. The aim of this research is to determine the influence of taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance at the Semarang Regency Samsat Office. The population of this research is all motor vehicle taxpayers in the jurisdiction of Semarang Regency totaling 559,805. The sample using the Slovin formula was 100. The data collection method used a questionnaire. The data analysis method used is multiple linear regression analysis, hypothesis testing, coefficient of determination test. The research results show that taxpayer awareness has a significant effect on taxpayer compliance and tax sanctions do not have a significant effect on taxpayer compliance. It is recommended that Semarang Regency Samsat further strengthen taxpayer awareness by providing good service to taxpayers. Increasing the quality and quantity of services is expected to increase satisfaction with taxpayers as customers thereby increasing taxpayer compliance. By increasing taxpayer compliance it will of course be easier to achieve the specified tax targets. Keyword: Taxpayer awareness, tax sanctions, taxpayer compliance